Characterization of the complete mitochondrial genome of Zhenhai brown frog Rana zhenhaiensis (Anura: Ranidae) - Huang, Min-Yi (Mitochondrial DNA B Resour, 2019)
Rana zhenhaiensis is a species of frog within the family Ranidae. In this study, its complete mitochondrial genome was characterized by high-throughput sequencing technology. It is 19,205 bp long with an overall AT content of 55.2% and includes 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes, and 1 control region. Besides, a 26-bp-long origin of L-strand replication (OL) is present between tRNA-Asn and tRNA-Cys. Our findings will be useful for the detailed study of mitogenome evolution and the phylogenetic relationships of the genus Rana and related taxa.